Aplastic anemia secondary to adjuvant Osimertinib therapy: a case report and a review of literature - Abdalhadi, Ahmed; Omar, Nabil E.; Kohla, Samah; Aakel, Hassan; Ekeibed, Yeslem; Mohsen, Reyad (Frontiers in Oncology, 2024)
Aplastic anemia is a rare hematological disorder characterized by suppressed hematopoiesis and pancytopenia. Although several drugs have been associated with aplastic anemia, its occurrence in response to Osimertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), is extremely rare. We present a case report of a 63-year-old patient with locally advanced non-small cell lung cancer (NSCLC) who developed aplastic anemia following adjuvant treatment with Osimertinib. Extensive investigations ruled out infectious etiology, and the absence of bone marrow involvement or other identifiable causes suggested a drug-induced etiology, specifically Osimertinib. This case report emphasizes the importance of recognizing this adverse event and considering it as a potential complication of Osimertinib therapy. Vigilant monitoring and prompt management are essential for optimizing patient outcomes. Further studies are needed to better understand the risk factors, underlying mechanisms, and management strategies for Osimertinib-induced aplastic anemia in the adjuvant settings.